Inclusive Teaching Strategy as a Reinforcement of Religious Moderation in Madrasah Ibtidaiyah, Teluk Nibung District - Emeliya Sukma Dara Damanik; Pangulu Abdul Karim (Universitas Muhammadiyah Enrekang, 2024)
This research aims to explore and analyze inclusive teaching strategies as a reinforcement of religious moderation in Madrasah Ibtidaiyah, Teluk Nibung Subdistrict. In the context of inclusive education, where students with diverse backgrounds and learning needs are taught together, this study focuses on the development of teaching methods that support religious moderation within the school environment. A qualitative research approach was employed to collect data through classroom observations, interviews with teachers and school staff, and analysis of documents related to the curriculum and inclusive teaching guidelines. The research findings indicate that inclusive teaching in Madrasah Ibtidaiyah, Teluk Nibung Subdistrict, has significantly contributed to religious moderation among students. Inclusive teaching strategies, such as cooperative learning, formative assessment, and curriculum adjustments, enable students from different religious backgrounds to learn together by understanding and respecting their differences. Furthermore, the active role of teachers in creating an inclusive learning environment strengthens religious moderation, reduces inter-religious tensions, and enhances religious understanding. This research provides in-depth insights into how inclusive teaching strategies can play a role as a reinforcement of religious moderation in Madrasah Ibtidaiyah. These findings offer valuable perspectives for the development of inclusive education and the cultivation of religious moderation within the school environment. Additionally, they serve as a foundation for further research in broader contexts.